Different methods of managing bluestem pasture - Smith, E.F.; Anderson, K.L.; DeGeer, C.V.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This experiment was to determine the effect of different stocking rates of deferred grazing, and of pasture burning on cattle performance productivity of pastures, and range condition as determine by plant population changes. In addition to the yearling report, a summary of cattle gains for the past 15 years included.
Keywords: Beef; Stocking rates; Range condition; Gain